Fostering Motivation: Exploring the Impact of ICTs on the Learning of Students with Autism - José María Fernández-Batanero; Marta Montenegro-Rueda; José Fernández-Cerero; Eloy López-Meneses (Children, 2024)
Currently, the use of digital tools has led to significant changes in the educational system, favouring equity and the inclusion of students with educational needs. In this context, students with autism spectrum disorder (ASD) benefit from using these electronic devices to improve their learning experience. This study focuses on conducting a bibliometric analysis of the impact of information and communication technologies on the learning of students with ASD, with the aim of addressing two research questions. Through the analysis of three databases (Scopus, Dialnet, and Web of Science), a total of 24 articles related to the subject were collected. The results show that the use of different technological devices has numerous benefits for these students. Among the most prominent are the use of augmented reality and educational robotics, mainly providing improvements in academic performance, motivation and improved retention of knowledge acquired in the classroom. In conclusion, the clear need to train teachers in digital competencies and to intensify efforts in this line of research in order to improve the education of students, as well as to enrich the knowledge available to the scientific community, is highlighted.